The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1590/1809-4430-eng.agric.v37n4p838-847/2017
|View full text |Cite
|
Sign up to set email alerts
|

Financial Analysis of the Investment in Precision Agriculture Techniques on Cotton Crop

Abstract: ABSTRACT:The aim of this study was to evaluate a financial analysis by the use of precision agriculture (PA) techniques on cotton crop. The experiment was carried out in a cotton field of 91 ha and its result compared to another field with similar area, cultivated with the conventional agricultural techniques. The financial analysis was extrapolated to the total farm area of 3,500 ha. All agricultural inputs applied, during the 2013/14 cotton crop season were analyzed, as well as their costs. The use of precis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 6 publications
1
7
0
Order By: Relevance
“…Furthermore, due to shared costs between project partners, ROI becomes a collective performance measure that can be estimated only when each member has acquired the according technological benefits. A complex profitability study is required to specify the precision service offerings, as presented in [55,56]. Each partner in the DIAS project owns and offers different assets in this endeavor, thus calculating the overall ROI of UAV usage from the side of farmers is not yet possible.…”
Section: Benefits and Costsmentioning
confidence: 99%
“…Furthermore, due to shared costs between project partners, ROI becomes a collective performance measure that can be estimated only when each member has acquired the according technological benefits. A complex profitability study is required to specify the precision service offerings, as presented in [55,56]. Each partner in the DIAS project owns and offers different assets in this endeavor, thus calculating the overall ROI of UAV usage from the side of farmers is not yet possible.…”
Section: Benefits and Costsmentioning
confidence: 99%
“…One of the tools that can be used to maximize cotton farmer profitability is precision agriculture. It consists of a series of management techniques performed accurately on smaller land units, unlike conventional management which considers an entire field as uniform area (Baio et al 2017). In economic terms, the use of this technology makes it possible to prioritize investments in areas where production potential is more effective, ensuring greater economic returns (Amaral et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…However, the modernization of agriculture and implementation of precision agriculture (PA) tools have shown that soil nutrient levels, nutrient amounts removed by plants, and nutrient losses are not uniformly distributed in the field (Molin, 2002, Mallarino & Wittry, 2004, Santi et al, 2012. Thus, geo-referenced soil sampling for recognizing the spatial variability of soil attributes and application of variable rates of fertilizers and correctives has been widely adopted in Brazil (Corá & Beraldo, 2006, Soares Filho & Cunha, 2015, Baio et al, 2017. Soil fertility mapping can optimize the use of agricultural inputs, increase crop yield, promote higher profitability for farmers and mitigate environmental impacts derived from agriculture (Mallarino & Wittry, 2004, Baio et al, 2017.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, geo-referenced soil sampling for recognizing the spatial variability of soil attributes and application of variable rates of fertilizers and correctives has been widely adopted in Brazil (Corá & Beraldo, 2006, Soares Filho & Cunha, 2015, Baio et al, 2017. Soil fertility mapping can optimize the use of agricultural inputs, increase crop yield, promote higher profitability for farmers and mitigate environmental impacts derived from agriculture (Mallarino & Wittry, 2004, Baio et al, 2017.…”
Section: Introductionmentioning
confidence: 99%